Effect of Y Addition on the Structural Properties and Oxidation Behavior of Fe60Al40-nYn Alloys (n= 1, 3, and 5 at.%). (4th May 2022) - Yildirim, Mehmet; Atas, Mehmet Sahin; Akdeniz, M. Vedat; Mekhrabov, Amdulla O.
ABSTRACT: The influence of Y addition on the microstructural features, phase relationships, hardness, magnetic behaviour and cyclic oxidation performance of Fe60 Al40 − n Y n alloys ( n = 1, 3, and 5 at.%) has been examined in detail. Al8 Fe4 Y phase formed even at 1 at.% Y addition because of the limited solid solubility of Y in the FeAl-based phase. For all the examined compositions, the Al8 Fe4 Y phase developed a eutectic with the FeAl-based phase and its volume fraction increased with increasing Y up to 5 at.%, which is near the eutectic composition. The mean microhardness values increased with increasing Y content for both as-cast and heat-treated samples. Cyclic oxidation tests revealed that the oxidation rate and scale thickness increased with increasing Y content. α-Al2 O3 was the main surface oxide for all compositions. θ-Al2 O3 was also formed with relatively low amount. An internal oxidation layer composed of mixed Al/Y oxides was observed beneath the surface layer.